The Collaborative Model In Indonesia Digital Media Landscape: Study Of Institutional Innovation In 'Close The Door’ - Mufti Nurlatifah (Profetik: Jurnal Komunikasi, 2025)
The digital environment provides opportunities for everyone and is anticipated to create more equitable sharing of power in society.  Unfortunately, with the growth of capital and monetization issues in the digital environment, control of the digital landscape by a number of parties is inevitable. This condition was identified in YouTube, one of the most influential digital platforms in Indonesia. Deddy Corbuzier is now known as the most popular YouTuber in Indonesia. Not only in terms of subscriber count and channel views, but also the composition of his institutional collaborator through Close The Door. A model that can be elaborated to describe how collaboration is created in the landscape of digital content producers in Indonesia. The institutional track record leveraging Deddy Corbuzier's fame has impacted  the development of the digital content industry.  From a political economy of media perspective, this condition portrays the paradoxical condition of content creators in Indonesia. First, similar to what happened in the traditional media business, the institutional ruler was established in Indonesia's digital landscape. Second, in the middle of uncertain conditions for content providers to survive, the institution creates a solution for digital media with a collaboration mechanism. This research was conducted through a desk study to examine how innovation was formed through collaboration among digital content creators. This study illustrates that while the digital media ecosystem helps content producers thrive initially, in the long run, it also promotes digital capitalization and the emergence of new rulers.